📚 og 📞 - En 😍 📖 - Hansen, Lone Koefoed (Passage - Tidsskrift for litteratur og kritik, 2014)
Lone Koefoed Hansen: “📚 and 📞: A 😍 📖” Reflecting on the intersections of literature and the smartphone language emoji, the essay discusses a range of contemporary examples of emoji literature as well as recent appropriations or translations of literature to emoji, often happening in spontaneous and short waves on social media.